Navigating the New Normal: Digital Proximity and JIT in Small Business Transformation - Ramírez Martínez Lucía; Durazo-Watanabe Eduardo; Izquierdo Camacho Juan Carlos (SHS Web of Conferences)
The COVID-19 outbreak has significantly impacted supply chains across various sectors. However, the healthcare sector, including dental services, has seen increased demand. This study proposes digital proximity as a new strategy for small and medium-sized enterprises (SMEs) to engage with their customers through digital channels. To implement this concept, the just-in-time methodology is recommended to optimize internal processes and compete with large e-commerce intermediaries. The key findings highlight a rise in demand for dental health services, particularly in dentistry, despite border closures. The United States remains the primary supplier of materials for the sector, underscoring limitations in the development of the local supply chain, which can be attributed to a lack of understanding of dental service providers’ needs. This study suggests digital proximity and just-in-time methodology as crucial strategies for SMEs to grow competitively at the regional level by fostering closer customer relationships, enabling faster adaptation to market needs, and improving process efficiency. In conclusion, these tools are essential for SME development in the dental service sector and their regional market expansion.